MEDAN ZOO TOURISM AREA DEVELOPMENT PLANNING USING SWOT ANALYSIS - Feby Milanie; Ruben Simangunsong; Sihar Sinurat; Novawati Siregar; Olivia Maria M Panjaitan; Jericho Alpasyakh H (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to researchMedan Zoo Tourism Area Development Planning Using SWOT Analysis.The type of research used in this research is descriptive research with a qualitative approach. The aim of descriptive research is to provide a factual and accurate description or presentation of the facts and characteristics of the research object according to what is being studied. The analysis method is in the form of system analysis using SWOT Analysis.The existing condition of the Medan Zoo (Medan Zoo) has the potential to be developed and can attract the attention of investors. This can be seen from the land which is quite large and has potential, the availability of service facilities such as canteens, prayer rooms, the availability of infrastructure such as clean water networks, drainage, roads and others. The problems that currently exist at the Medan Zoo (Medan Zoo) are the lack of diversity of animals available, the lack of other supporting tourist attractions, the lack of awareness of visitors to dispose of rubbish in the right place, the condition of animal enclosures that are not well maintained, and the disposal of animal waste has not been properly planned. resulting in an unpleasant odor that can cause discomfort, poor drainage network system.